P0459ADULT MINIMAL CHANGE DISEASE IN TURKEY: THE RESULTS OF TURKISH SOCIETY OF NEPHROLOGY GLOMERULAR DISEASES WORKING GROUP. (6th June 2020) - Yılmaz, Mürvet; Sipahioğlu, Murat; Dervişoğlu, Erkan; Aydemir, Nihal; Uzun, Sami; Istemihan, Zulal; Unsal, Oktay; Tatar, Erhan; Berktas, Hacı Bayram; Ozdemir Kayalar, Arzu; Sumnu, Abdullah; Kumru Şahin, Gizem; et al.
Abstract: Background and Aims: Minimal change disease (MCD) is the most common cause of the nephrotic syndrome (NS) in children. Although there are many data regarding the course, response to treatment, and outcomes in pediatric patients, only a few series have examined these issues in adults. The aim of the study was to delineate the demographic and clinical properties of MCD of adult population in our country. Method: All over the country, a total of 47 centers entered data between May 2009 and May 2019 to the database created by of Turkish Society of Nephrology Glomerular Diseases (TSN-GOLD) Working Group. Demographic and clinical characteristics and biopsy findings recorded to the database were analyzed. Results: In total, 258 patients were compatible with the pathological diagnosis of MCD. Mean age was 36.16±15.44 years and 53.88% were male. At diagnosis, 66.7% patients presented with pretibial edema, 15.9% with hypertension. Microscopic hematuria occured in 18.2% patients. Only 24 patients (9.3%) presented with a decrease in renal function (serum creatinine greater than 1.3 mg/dl). The mean daily proteinuria was 6.3 g, and serum albumin was 2.6 mg/dl. The most frequent indication for biopsy was NS (86.4%). On kidney biopsy, the mean number of glomeruli was 18.08±11.11. Mezangial proliferation and mezangial IgM were present in 27.5% and 22.5%, respectively. Only in 3.5% of the included patients, electron microscopic studies were performed. Conclusion: This study describes the characteristics of a cohort of adult patients with MCD. MCD in adults may sometimes present concurrently with hematuria, hypertension, and acute kidney injury.